Collaborative Governance: Trust Building Indicators in The “Fish Apartment” Community Empowerment Area Development (Cead) : Program in Malili District - Hidayat, Muhammad Hidayat Djabbari; Jeri M; Robby (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
The trust-building indicator is one of the stages in the collaboration process that considers collaboration to be more than just negotiations among various stakeholders. Beyond that, it is an effort to mutually build trust. Building trust is crucial and should be done as early as possible when the collaboration process begins to prevent egoism among the various institutions or organizations involved. The purpose of this research is to understand the collaborative governance process by analyzing the trust-building indicator in the implementation of the Community Empowerment Area Development Program through the "Apartemen Ikan" program in Malili sub-district. The research method used a qualitative approach, with data collected through interviews, field observations, and document reviews. The data obtained were analyzed through several stages: data reduction, data display, and conclusion drawing and verification. The informant determination technique used purposive sampling, with informants in this study being: 1) Regional Secretary of East Luwu Regency; 2) Head of Community and Village Empowerment Office of East Luwu Regency; 3) Director of Communications and External Relations of PT. Vale Indonesia, Tbk; and 4) Coastal Communities. The research results indicate that the trust-building indicator in the implementation of the Community Empowerment Area Development Program through the "Apartemen Ikan" program in Malili sub-district, East Luwu Regency, is influenced by several factors, namely: 1) The "Apartemen Ikan" program is discussed collectively by all parties in meetings and deliberations; 2) awareness of the initial collaboration goals; 3) the existence of jealousy among villages and communities (sectoral ego); 4) conflict of interest in providing assistance; 5) insufficient quality of human resources; 6) joint commitment to completing the program is lacking; 7) responsiveness of the budget from PT. Vale; and 8) lack of transparency in CSR budgeting. Therefore, the trust established among stakeholders is considered insufficient.